Need some protips.

p<--> (t v s) is a premise, does that mean I can substitute p into any other premise that contains (t v s), and vice versa? (I'm quite sure this is the case)

After having done the substitution what happens to the p<--> (t v s) expression?

eg.

p v (-q)

(t v s) --> (p v r)

(-r) v (t v s)

p <--> (t v s)

_______________

(p n r) --> (q n r)

First step, and this is where I get confused, the logic after this is pretty easy, and without having done a truth table I believe that the argument is invalid.

p v (-q)

p --> (p v r)

(-r) v (p)

???????????

___________

(p n r) --> (q n r)

AHHHH!